2000
DOI: 10.1089/15246090050147745
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Functional Capacity Measurement in Women: A Report from the NHLBI-Sponsored WISE Study

Abstract: Physical activity and functional capacity have not been assessed by questionnaire for criterion validity in women. We wished to evaluate the ability of a physical activity and a functional capacity assessment questionnaire to predict functional capacity measured by treadmill exercise stress testing, as well as correlate with cardiac risk factors and angiographic coronary artery disease (CAD) in women. In a National Heart, Lung and Blood Institute (NHLBI)-sponsored cross-sectional population study involving fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
1
32
0
2
Order By: Relevance
“…Participants were asked about their ability to perform common activities of daily living, such as personal care, ambulation, household tasks, sexual function, and recreational activities, which are each associated with specific metabolic equivalents (METs). This valid and common tool correlates with treadmill functional capacity measured in METs [36] and also correlates highly with peak oxygen uptake [37]. The validity of the scale is demonstrated by such strong correlations with peak oxygen uptake.…”
Section: Clinicalmentioning
confidence: 75%
“…Participants were asked about their ability to perform common activities of daily living, such as personal care, ambulation, household tasks, sexual function, and recreational activities, which are each associated with specific metabolic equivalents (METs). This valid and common tool correlates with treadmill functional capacity measured in METs [36] and also correlates highly with peak oxygen uptake [37]. The validity of the scale is demonstrated by such strong correlations with peak oxygen uptake.…”
Section: Clinicalmentioning
confidence: 75%
“…BMI was calculated as the weight in kilograms divided by the square of height in meters. Patients 21 Physical activity was determined through the Postmenopausal Estrogen and Progesterone Intervention questionnaire (PEPI-Q). 21 The scores on the PEPI-Q range from 1-12, with higher scores indicating higher levels of physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…Patients 21 Physical activity was determined through the Postmenopausal Estrogen and Progesterone Intervention questionnaire (PEPI-Q). 21 The scores on the PEPI-Q range from 1-12, with higher scores indicating higher levels of physical activity. Functional capacity was assessed through the Duke Activity Status Index (DASI) questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,27,31,32 Unlike physical fitness, which can be objectively measured, physical activity is a behavior, and how well it correlates with exercise capacity has not been extensively validated. 16,[33][34][35][36] Two studies that focused on women were based on the Framingham Heart Study 32 and the Women's Health Initiative (WHI) Observational Study. 31 The Framingham Heart Study demonstrated a relation between physical activity and all-cause death.…”
Section: Gulati Et Al Exercise Capacity and Risk Of Death In Womenmentioning
confidence: 99%